Investigation on Flexible Float - A Canvas Headline Lifting Device for Trawls - K.K., Kunjipalu; M.R., Boopendranath (Fishery Technology, 2025)
Performance of 'flexible float', a newly developed two panelled canvas headline lifting device for trawls, has been evaluated Â through field trials in the waters off Cochin, India, during 1986-90. Statistically significant improvement in the yield of finfish by 115.9% and total catch by 69.0% were obtained a 40 m demersal trawl when rigged with flexible float. Similarly, a 32 m high opening trawl registered a significant improvement in the yield of finfish and total catch by 23.2 and 27.8% respectively. Difference in the catch of crustaceans and cephalopods in both the gears, were not statistically significant. Improved fishing performances is attributed to higher headline lift coupled with enhanced herding effect on the finfish components in the vicinity of trawl mouth caused by addition of visually conspicuous flexible float. PVC-coated nylon fabric which is indigenously produced, has been identified as a suitable material for fabrication of flexible float in view of its improved tesnile strength and resistance to bio-degradation in marine conditions, compared to cotton canvas.